Separation of ternary liquid systems by molecular and ionic interaction modification with modeling - Dugos, Nathaniel P. (Animo Repository, 2008)
The semiconductor and optical industries generate large amounts of spent solvents per year. These spent solvents are composed of about 90% organic solvents such as isopropyl alcohol (IPA), toluene, acetone, methyl ethyl ketone (MEK) and ethanol. The spent solvents are wastes in the cleaning process. They are mixtures of solvents that are used in removing dirt, grease, and waxes and usually mixed with minimal quantity of water. At present they are handled like special wastewater and treated accordingly. However, this treatment method is feasible only when small amount of spent solvents are to be disposed of. Since 12000 metric tons are generated annually by the Philippine industries and the volume is steadily increasing, this traditional method is no longer viable due to its adverse effects on the environment, health and safety. Solvent recovery by conventional distillation is the best option to recover and re-use the constituent solvents of the spent solvent system. But the conventional distillation of this nonideal system to produce high purity solvents is limited by the formation of the azeotrope. Hence, in this study the idea of adding an ionic salt to the spent solvent system so as to enhance the separation by traditional distillation was tested. Specifically, the effect of the type and concentration of the salt on the boiling point and VLE were investigated. The test spent solvent system is a ternary mixture composed of toluene, IPA and water with the concentration of water fixed at 10% by volume. Different amounts of salts (NaCl, CaCl2, MgCl2, CuCl2, Na2SO4) were separately added to each of the prepared ternary mixture to fix the desired molality of the salt. Experiments performed were the boiling point determination, generation of the VLE data using the ebulliometer and batch simple salt distillation. Based on the results, all the salts were found to be capable of lowering the boiling point of the ternary system studied and the lowering is more pronounced at the higher concentration of the salt. Sodium sulfate was the most effective in lowering the boiling point of the system. Although the lowering in the boiling point of the solutions with salt was not statistically significant, a decrease of about 1-4oC is an interesting result. Distillation at lower temperatures means substantial amounts of energy will be saved making the process economical. Another valuable result is the increase in the concentration of the nonpolar substance (toluene) in the vapor phase when salt was added. Water, being a polar molecule, is ii attracted to the salt resulting in the lowering of its vapor pressure. The higher the concentration of the ions present in the solution, the greater the amount of toluene that will be separated from the solution. Experimental results on the VLE proved this hypothesis. All the solutions with salt showed a higher toluene concentration in the vapor phase than its equilibrium liquid. Also the presence of the salt in the solution has a very significant effect on the relative volatility of the solvents. The relative volatility of toluene to IPA increased to about 4 to 10 times. The saltingout of toluene was largest with Na2SO4 and the lowest, with NaCl. For the salts that do not hydrolyze the salting-out is in the order MgCl2, CaCl2 and NaCl, with MgCl2 the highest. This finding opens the possibility of using molecular and ionic interaction modification for selective separation of multi-component system. Results of the batch simple distillation of the solution with NaCl showed also an increase in the concentration of toluene in the distillates. All the distillate fractions collected indicated that the product were practically mixtures of IPA and toluene, most of the toluene coming from the first few fractions. Furthermore, the boiling point profiles showed a decreasing boiling point for the first four distillate fractions. This is a manifestation that most of the toluene is vaporized in this stage. Experiments on the VLE determination of the system in the absence and in the presence of MgCl2 revealed that increasing the salt concentration decreased appreciably the mole fraction of water in the vapor phase. The enhancement factor increased strongly with increasing MgCl2 concentration attaining values as high as 6.5. The degree of enhancement was found to be most pronounced at higher concentration of IPA and at higher concentration of MgCl2 in the feed. The UNIQUAC model was able to give very satisfactory correlation of the experimental VLE data of the mixed-solvent system without salt. For the system with 1.0 m MgCl2, the Extended UNIQUAC model predicted quite well the VLE of the system. For the system with 0.2 m MgCl2, a high linear correlation between the experimental and calculated vapor composition was observed. However for the boiling point the fitting is just satisfactory